International Travelers' Sociodemographic, Health, and Travel Characteristics: An Italian Study - Gianmarco Troiano; Astrid Mercone; Alessandra Bagnoli; Nicola Nante (Ubiquity Press, 2017)
Background: Approximately the 8% of travelers requires medical care, with the diagnosis of a vaccine-preventable disease. The aim of our study was to analyze the socio-demographic, health and travel characteristics of the Italian international travelers. Methods: We conducted a cross sectional study from January 2015 to June 2016, at the Travel Medicine Clinic of Siena, asking the doctor to interview patients who attended the Clinic, recording socio-demographic and travel information, malaria prophylaxis, vaccinations. The data were organized in a database and processed by software Stata®. Results: We collected 419 questionnaires. Patients chose 71 countries for their travels; the favorite destinations were: India (6.31%), Thailand (6.31%), and Brazil (5.10%). The mean length of stay was 36.17 days. Italians, students, and freelancers tended to stay abroad for a longer time (mean: 36.4 days, 59.87 days and 64.16 days respectively). 33.17% of our sample used drugs for malaria chemoprophylaxis: 71.9% of them used Atovaquone/Proguanil (Malarone®), 26.6% used Mefloquine (Lariam®), 1.5% other drugs. The vaccinations that travelers mostly got in our study were to prevent hepatitis A (n = 264), the typhoid fever (n = 187), the Tetanus + Diphtheria + Pertussis (n = 165), the Yellow fever (n = 118) and the cholera (n = 78). Twenty-eight (6.68%) refused some recommended vaccinations. The vaccines mostly refused were for Typhoid fever (n = 20), hepatitis a (n = 9), and cholera (n = 9). Conclusion: Our results demonstrated that Italian international travelers are at-risk because of their poor vaccinations adherence. This implies that pre-travel counseling is fundamental to increase the knowledge of the risks and the compliance of future travelers.